STUDI FENOMENOLOGI HUBUNGAN INTERPERSONAL PERAWAT-PASIEN DENGAN PELAYANAN KEGAWAT- DARURATAN DI INSTALASI GAWAT DARURAT RSUD H. ANDI SULTHAN DAENG RADJA BULUKUMBA - Abdul Rahman; Ismail Said; Rohana Thahier (Politeknik STIA LAN Makassar, 2020)
Emergency nurses are those who interact firstly with patients who need continuous care from healthcare providers. With high numbers of patients, high level of workload, and also high-paced and stressful working environment, these nurses are demanded to be professional. Unfortunately, literature discussing the nurses’ experiences regarding emergency care has been lacking. This study used qualitative method with phenomenology research design. The data was obtained through in-depth interview, by which interview guidance was used as primary instrument. This study involved 6 (six) nurses from emergency department of the hospital that consisted of one chief nurse and five charging nurses. This study resulted in three themes, including emergency room nurses experience, interpersonal relationships of nurse-patient/ family, and also emergency nurses hopes. The first theme resulted in subthemes: (1) emergency nurses felt uniqueness, (2) satisfying experience and motivated, (3) unpleasant experiences. The second theme included subthemes: (1) interpersonal relationships between nurses and patients/ families were important, (2) all respondents lack of knowledge regarding Peplau’s Theory of Interpersonal Relationship. The third theme resulted in subthemes: (1) Hopes related to prosperity or salary, and (2) wishes regarding continuous education and trainings. This study recommended revision of operational standard of patient reception in emergency room, provision of reporting sheet regarding violence to helatcare providers, complaint management training, endeavors to increase nurses’ salary, and continuous education training for emergency nurses.